Analisis Ruang Lingkup Psikologi Belajar: Konsep, Metode, dan Implikasinya dalam Meningkatkan Efektivitas Pembelajaran - Arifah Elwahdiyah; Muslim Afandi; Mhd Subhan (Lembaga Intelektual Muda (LIM) Maluku, 2026)
Learning psychology is a branch of science that plays a crucial role in understanding students' learning processes. In educational practice, some learning approaches still do not fully consider psychological aspects, resulting in suboptimal learning outcomes. Therefore, understanding the scope of learning psychology is crucial, particularly in the context of Islamic Religious Education. This study aims to describe and analyze the scope of learning psychology, including its definition, methods, and benefits in improving learning effectiveness. This study employed a qualitative approach with library research, using books, scientific journal articles, and relevant previous research as data sources. Data collection was conducted through documentation studies, while data analysis employed descriptive qualitative analysis techniques. The results show that learning psychology addresses not only changes in individual behavior during the learning process but also encompasses cognitive, affective, and psychomotor aspects influenced by various internal and external factors. Furthermore, learning psychology employs a variety of methods, such as clinical methods, questionnaires, experiments, case studies, and tests, that can be used to gain a deeper understanding of students' conditions. An understanding of learning psychology also provides significant benefits for educators in designing effective learning, creating a conducive learning environment, and optimally developing students' potential